General practitioner and pharmacist collaboration: does this improve risk factors for cardiovascular disease and diabetes? A systematic review protocol - Rohina Joshi; Kanika Chaudhri; Adina Hayek; Hueiming Liu (BMJ Open)
Introduction Cardiovascular disease (CVD) remains a major cause of morbidity and premature mortality globally. Despite the availability of low-cost evidence based medicines, there is a significant treatment gap in those with established or at high risk of CVD in the primary care setting. Pharmacist-based interventions have shown to improve patient outcomes for many chronic diseases including CVD. However, there is little synthesised evidence that has examined the effects of collaborative care between general practitioners (GPs) and pharmacists on patients’ cardiovascular risk outcomes. This protocol aims to outline the methods employed in a systematic review of current literature to assess whether interprofessional collaboration between GPs and pharmacists has an impact on improving cardiovascular risk outcomes among patients in the primary care setting.Methods and analysis Randomised controlled trials (RCTs) will be identified through database searches, scanning reference lists of relevant studies, hand searching of key journals and citation searching of key papers. Two independent reviewers will screen studies against eligibility criteria and extract data using standardised forms. Databases including MEDLINE, EMBASE, Cochrane, CINAHL and International Pharmaceutical Abstracts, will be searched from the beginning of each database until October 2018. Primary outcome includes improvement in cardiovascular risk factors, such as hypertension, due to GP and pharmacist cooperation. Secondary outcome is to describe the different types of GP and pharmacist collaborative models of care. A narrative synthesis of findings will be presented. A meta-analysis will be performed if the data are homogenous.Ethics and dissemination This study does not require ethics approval. The results of the systematic review described within this protocol will be disseminated through presentations at relevant conferences and publication in a peer-reviewed journal. The methods will be used to inform future reviews.PROSPERO registration number CRD42017055259.